O marketing de experiência e o novo consumidor: um estudo bibliográfico - Manchon, Polianna Negri [UNESP] (2015)
This study aims to elucidate the marketing experience and to show the fundamental role that strategic communication plays as a tool for approaching the target audience and for consolidating a brand. The necessity for differentiation and innovation increases with market competition, standardization of products and services and with a customer more demanding and careful, leading the sensorial experiences to a trend of communication capable of bringing closer the relation between consumer and brand. From a bibliography research, marketing concepts, public relations and marketing experience are studied, presenting national and international cases of success in the retail industry. The study focuses on the comprehension of actions that leads to experiences in the market environment